Implementation of Industrial Internet of Things-Based Scalar Control Method Using PID Controller for Multiple Three-Phase Induction Motor Control - Angga Wahyu Aditya; Restu Mukti Utomo; Nur Rani Alham; Faisal Faizz Ramadhanu (Journal of Renewable Energy, Electrical, and Computer Engineering, 2024)
Developing industrial standard induction motor control devices is inseparable from the advantages and ease of implementation. Induction motor control has developed rapidly since the development of semiconductor technology, which allows for more efficient, flexible, and accessible settings. The third industrial revolution makes it easier to control induction motors by meeting device standards and data communication systems. The development of cloud technology and the industrial Internet of Things in the fourth industrial revolution makes it easier to quickly control multiple induction motors from various places. Industry-standard devices such as human-machine interface, programmable logic control, and inverters are used to determine the performance of multiple induction motors using a scalar method based on PID controllers with a mobile phone remote control. PID performance is analyzed under transient conditions by measuring the rise time value and overshoot percentage. Meanwhile, the parameters measured in steady-state conditions are the average steady-state error values. The parameters on the PID controller are adjusted intuitively. The parameters used in data collection consist of the first parameter with the value of  Kp=26,  Ki=14, and  Kd=12, and the second parameter with the value of  Kp=29,  Ki=15, and  Kd=0. The rise time value will increase along with the given speed reference. The overshoot percentage value depends on the speed reference and the PID parameter value. At the same time, the average steady-state error value is below 5% for almost all speed references under loaded and unloaded conditions.